Hedgehog signaling in endocrine and folliculo-stellate cells of the adult pituitary. Issue 3 (March 2021) - Botermann, Dominik Simon; Brandes, Nadine; Frommhold, Anke; Heß, Ina; Wolff, Alexander; Zibat, Arne; Hahn, Heidi; Buslei, Rolf; Uhmann, Anja
Abstract : Ubiquitous overactivation of Hedgehog signaling in adult pituitaries results in increased expression of proopiomelanocortin ( Pomc ), growth hormone ( Gh ) and prolactin ( Prl ), elevated adrenocorticotropic hormone (Acth) production and proliferation of Sox2 + cells. Moreover, ACTH, GH and PRL-expressing human pituitary adenomas strongly express the Hedgehog target GLI1. Accordingly, Hedgehog signaling seems to play an important role in pathology and probably also in homeostasis of the adult hypophysis. However, the specific Hedgehog-responsive pituitary cell type has not yet been identified. We here investigated the Hedgehog pathway activation status and the effects of deregulated Hedgehog signaling cell-specifically in endocrine and non-endocrine pituitary cells. We demonstrate that Hedgehog signaling is unimportant for the homeostasis of corticotrophs, whereas it is active in subpopulations of somatotrophs and folliculo-stellate cells in vivo . Reinforcement of Hedgehog signaling activity in folliculo-stellate cells stimulates growth hormone production/release from somatotrophs in a paracrine manner, which most likely is mediated by the neuropeptide vasoactive intestinal peptide. Overall, our data show that Hedgehog signaling affects the homeostasis of pituitary hormone production via folliculo-stellate cell-mediated regulation of growth hormone production/secretion.